Maize Milling and Modifying Atmospheric Conditions Limit Formation of Aflatoxin B1 by Aspergillus Flavus - Temba, Benigni Alfred; Bakari, Gaymary George (Journal of Biology and Life Science, 2021)
Occurrence of mycotoxins in foods poses a serious health concern all over the world. Aflatoxin B1 (AFB1) is the most toxic, with widest occurrence in various foods, but mainly in cereals and nuts and its accumulation depends on substrate and environmental factors. This study investigated the how physical status (milling) of maize kernels and atmospheric conditions (aeration, moisture and temperature) affect production of aflatoxin B1 by Aspergillus flavus (ATCC 28862). Intact kernels and flour were incubated for up to 20 days in open and partially sealed petri dishes under controlled temperatures of 25 ºC, 30 ºC and 37 ºC and initial moisture contents of 27%, 22%, 18%, 15% and 12%. It was found that on average, significantly higher (p < 0.05) aflatoxin B1 level was accumulated in intact kernels (145.7 µg/kg) as compared to milled kernels (2.2 µg/kg). Also, none of the samples incubated under partially sealed conditions, compared to up to 100% of the samples incubated in open atmosphere had detectable levels of aflatoxin B1 after 20 days. Fungal growth was not affected by milling or aeration, but sporulation was low at 37 ºC and high at 25 ºC and 30 ºC. The findings of this study provide baseline information on how conditions can be modified to control postharvest accumulation of aflatoxin B1 in cereals.